2006
DOI: 10.1149/1.2355776
|View full text |Cite
|
Sign up to set email alerts
|

From Smart-Cut to Soft-Cut: Mechanisms of Hydrogen Plasma Supported Layer Exfoliation in Silicon

Abstract: Comparative investigations of silicon layer exfoliation within the Smart-Cut process and its progression at lower H+ implantation doses and subsequent H-plasma exposure (Soft-Cut) were done by µ-Raman spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM) on (100)-oriented Cz Si wafers. Blister formation and evolution at various process temperatures were analyzed to clarify the mechanisms of layer exfoliation for both approaches. On base of the Raman analyses and supporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…One might speculate that either another type of hydrogenated vacancy defect complex now comes into play, or the electrically inactive defects -e. g. V-H 4 -are transformed back again to an electrically active defect state by a release of hydrogen. The latter explanation was ruled out, since we recently observed that fully hydrogenated vacancy complexes such as V-H 4 are stable at least up to 500 °C (14). Hence, we supposed that oxygen-related complexes, for example, hydrogenated V x -O y -H z complexes -might cause the enhanced n-type doping around R p .…”
Section: He + -Implantation and Subsequent H-plasma Treatmentmentioning
confidence: 97%
“…One might speculate that either another type of hydrogenated vacancy defect complex now comes into play, or the electrically inactive defects -e. g. V-H 4 -are transformed back again to an electrically active defect state by a release of hydrogen. The latter explanation was ruled out, since we recently observed that fully hydrogenated vacancy complexes such as V-H 4 are stable at least up to 500 °C (14). Hence, we supposed that oxygen-related complexes, for example, hydrogenated V x -O y -H z complexes -might cause the enhanced n-type doping around R p .…”
Section: He + -Implantation and Subsequent H-plasma Treatmentmentioning
confidence: 97%
“…Furthermore, in the fabrication of MEMS, photonics and THz devices, costly SOI wafers or successive deposition/isolation/etching of sacrificial layers are frequently used to float the structures where needed [15]. On the other hand, there is a technique called soft-cut reported in [16] where lower doses of hydrogen implantation is used to fabricate SOI structures and a plasma hydrogenation step is employed to compensate the lower doses.…”
Section: Introductionmentioning
confidence: 99%